Fulvifomes aurantiacus sp. nov. (Basidiomycota; Hymenochaetaceae) from Pakistan - Fatima, Maham; Usman, Muhammad; Khalid, Abdul Nasir (Phytotaxa, 2023)
The present study is the first report dealing with Pakistani Fulvifomes species. A new species, Fulvifomes aurantiacus, is identified on the basis of morpho-anatomical and phylogenetic analyses from Lahore, Pakistan. The species is characterized by pileate to sub-stipitate, basidiocarps having orange-brown pileal surface with yellow ocher wide zones and velutinous poroid hymenophore; 4–5 pores per millimeter, the presence of duplex context, dimitic hyphal system, absence of hymenial setae and the presence of contextual gleoplerous hyphae and highly pigmented ovoid to sub-globose basidiospores, 4.4–6.7 × 3.75–5.8 μm. Phylogenetically, our species formed a distinct clade with other Fulvifomes species, indicating its distinct position in the genus.